Primary and memory immune responses against rough Brucella canis are less robust compared to smooth B. abortus and B. melitensis following intratracheal infection in mice - Stranahan, Lauren W.; Garcia-Gonzalez, Daniel G.; Hensel, Martha E.; Arenas-Gamboa, Angela M. (Frontiers in Immunology, 2022)
Brucella canis is the cause of canine brucellosis, a globally distributed, zoonotic pathogen which primarily causes disease in dogs. B. canis is unique amongst the zoonotic Brucella spp. with its rough lipopolysaccharide, a trait typically associated with attenuation in gram-negative bacteria. Unfortunately, no vaccine is available against B. canis, and vaccine development is hampered by a limited understanding of the immune response required to combat it and the course of infection following a physiologically relevant, mucosal route of inoculation. To address these concerns and analyze the impact of the rough phenotype on the immune response, we infected mice intratracheally with rough B. canis or smooth B. melitensis or B. abortus. Bacterial colonization and histologic lesions were assessed in systemic target organs as well as locally in the lungs and draining mediastinal lymph node. Mice were also reinfected with Brucella following antibiotic treatment and cytokine production by T lymphocytes in the lung and spleen was assessed by flow cytometry to investigate the memory immune response. Despite its rough phenotype, B. canis established a persistent infection at the same level of colonization as the smooth strains. However, B. canis induced significantly less granulomatous inflammation in the spleen as well as a lack of bronchial-associated lymphoid tissue (BALT) hyperplasia in the lungs. These differences coincided with increased IL-10 and decreased IFN-γ in the spleen of B. canis-infected mice. Previous exposure to all Brucella strains provided protection against colonization following secondary challenge, although induction of IFN-γ by T lymphocytes was seen only in the lungs during B. canis infection while the smooth strains induced this cytokine in the spleen as well. Neither Brucella strain induced significant polyfunctional T lymphocytes, a potential immunomodulatory mechanism that appears to be independent of lipopolysaccharide phenotype.